Unconfined Compressive Strength (UCS) of Soft Clay Stabilize with Coffee Ground for Batu Pahat Soft Clay - Shamsul, Adlin Nur Liyana; Zulkifli, Nur Ellysha; Ramli, Siti Hazzirah; Mokhtar, Mardiha (Multidisciplinary Applied Research and Innovation, 2025)
Soil stabilisation using food waste compost has been used for the improvement of soft soil, in improving the shear strength and limiting the deformation behaviours. In this research, composition treatment has been found to be very helpful in the process of improving soft soil characteristics. The aim of this study is to determine the successfullness potential of coffee grounds and the posibility has been tested through Unconfined Compressive Strength (UCS) test. The overall result that were obtained showed the improvements in soil’s physical properties, strength and stability and it was resulted in the change of category from very soft soil to soft soil. The results has proven that coffee ground is a good additives to increase the strength of soft soil and its stabilization.